Prevalence and associated factors of emotional and behavioral problems in Indonesian early adolescents: A cross-sectional study - Sundari, Ririn Isma; Sitaresmi, Mei Neni; Lusmilasari, Lely (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Emotional and behavioral problems (EBPs) in early adolescence are a growing public health concern, particularly in low- and middle-income countries like Indonesia. The COVID-19 pandemic has further disrupted adolescent development, highlighting the need to identify both internal and external contributing factors to these issues. Objective: This study aimed to assess the prevalence of emotional and behavioral problems among early adolescents in Central Java, Indonesia, and to identify internal and external factors associated with these problems during the post-pandemic transition from hybrid to offline learning. Methods: A cross-sectional study was conducted from May to June 2023 involving 256 adolescents aged 10–14 years in Central Java. Emotional and behavioral problems were measured using the Strengths and Difficulties Questionnaire – Self-Report (SDQ-SR). Internal factors were assessed using the Reduced Morningness–Eveningness Questionnaire (rMEQ) and the Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA). External factors were measured through sociodemographic questionnaires and the Revised Family Communication Pattern (rFCP) Scale. Descriptive statistics were used to characterize the sample. Associations were analyzed using multiple logistic regression, and model fit was assessed using the Hosmer–Lemeshow test and Nagelkerke R². Results: The prevalence of adolescents with abnormal total difficulties scores was 15.6%. Among SDQ subscales, emotional problems showed the highest abnormal prevalence (30.1%), followed by peer problems (10.9%), conduct problems (10.5%), and hyperactivity-inattention (4.3%). Multivariate logistic regression analysis revealed that adolescents with an eveningness chronotype were significantly more likely to experience EBPs (OR = 21.11, 95% CI: 5.82–76.63, p <0.001). Similarly, low emotional regulation increased the risk (OR = 5.08, 95% CI: 2.18–11.80, p <0.001). Among external factors, low maternal education (OR = 1.34, 95% CI: 1.12–1.94, p = 0.015) and low intrafamilial communication (OR = 3.35, 95% CI: 1.45–7.74, p = 0.004) were also significant predictors. The model showed good fit (Hosmer–Lemeshow χ² = 6.050, p = 0.642) and explained 40.6% of the variance in EBPs (Nagelkerke R² = 0.406). Conclusion: Emotional and behavioral problems remain a concern among Indonesian early adolescents in the post-pandemic, with emotional symptoms being the most prevalent. Internal risk factors, such as eveningness chronotype and low emotional regulation, as well as external factors like maternal education level and intrafamilial communication, were significantly associated with these issues. These findings suggest a need for early mental health screening and targeted interventions. For nursing practice, this highlights the role of nurses in school and community settings in promoting emotional regulation, strengthening family communication, and delivering health education tailored to familial and developmental contexts.